Quantification of the carbon bonding state in amorphous carbon materials: A comparison between EELS and NEXAFS measurements. (March 2021) - Mangolini, Filippo; Li, Zixuan; Marcus, Matthew A.; Schneider, Reinhard; Dienwiebel, Martin
Abstract: The quantitative determination of the carbon hybridization is critical for establishing processing-structure-properties relationships for carbon-based materials, including amorphous carbon coatings. While several techniques have been employed to characterize the amount of sp 2 and sp 3 carbon in these materials, direct comparisons between analytical results are limited. Here, we compare near edge X-ray absorption fine structure (NEXAFS) spectra of a silicon- and oxygen-containing hydrogenated amorphous carbon (a-C:H:Si:O) coating acquired in synchrotron-based scanning transmission X-ray microscopy (STXM) mode with electron energy loss spectra (EELS) obtained from the same a-C:H:Si:O lamella. While the fractions of sp 2 carbon computed from STXM and EELS spectra are in close agreement, the comparison of NEXAFS spectra acquired in STXM mode with NEXAFS spectra collected in partial electron yield mode on a flat a-C:H:Si:O surface indicated that the destructive preparation of thin lamellae for STXM analyses induces variations in the structure of a-C:H:Si:O, namely the breakage of carbon-silicon and carbon-hydrogen bonds, a change in ordering of sp 2 -bonded carbon, and an increase in the sp 2 carbon fraction. These findings can help scientists in the careful interpretation of spectroscopic results obtained from the analysis of samples made of metastable materials after the destructive preparation of specimens for analytical purposes. Graphical abstract: Image 1